Attention-deficit/hyperactivity disorder is associated with baseline child sport concussion assessment tool third edition scores in child hockey players. (19th September 2017) - Collings, Laurel J.; Cook, Nathan E.; Porter, Shaun; Kusch, Cody; Sun, Jonathan; Virji-Babul, Naznin; Iverson, Grant L.; Panenka, William J.
ABSTRACT: Objectives: The objectives of this study were to report baseline, preseason data for the Child-SCAT3, stratified by attention deficit hyperactivity disorder (ADHD) status, and examine group differences in Child-SCAT3 performance between children with and without ADHD. Design: Cross-sectional study. Methods: Young male hockey players (n = 304), aged 8–12 years, were administered the Child-SCAT3 during pre-season. Child-SCAT3 measures included a 20-item symptom scale, a Standardised Assessment of Concussion Child Version (SAC-C), a modified Balance Error Scoring System (m-BESS), a tandem gait task, and a coordination test. Results: Children with ADHD (n = 20) endorsed significantly more symptoms ( d = 0.95) and greater symptom severity ( d = 1.13) compared to children without ADHD. No statistically significant differences were found between groups on Child-SCAT3 measures of cognitive or physical functioning (e.g. balance and coordination). Conclusions: ADHD should be considered when interpreting Child-SCAT3 scores, especially symptom reporting, in the context of concussion assessment. Better understanding of symptom reporting in uninjured child athletes with ADHD can inform the clinical interpretation of symptoms at baseline and following an actual or suspected concussion. Normative data for the Child-SCAT3 that is not stratified by or otherwise accounts for ADHD status should be used with caution when appraising performance of children with ADHD.